The use of cable power lines in power supply systems of railways - A. V. Kryukov; K. V. Suslov; A. V. Cherepanov; I. A. Fesak (Вестник Северо-Кавказского федерального университета)
Introduction. Overhead power lines are traditionally used to connect railway traction substations to 110-220 kV networks. This approach has a number of disadvantages that can be eliminated when using 110-220 kV cables with molecular cross-linked polyethylene insulation in external power supply systems for traction substations. Goal. To develop digital models to determine the modes of railway power supply systems with power supply to traction substations via cables. Materials and methods.. Methods of multiphase modeling of electrical power systems and the Fazonord software product, version 5.3.4.5–2024 were used. Results and discussion. A comparison of the 110 kV AS-300 overhead line and a cable of a similar cross-section showed that in the case of a cable line, the standard deviations of voltages on the current collectors of electric locomotives were reduced by approximately 75%. Negative sequence asymmetry is reduced by 3...5 times, however, due to capacitive generation by cables, currents at low loads and losses in power lines increase. Conclusion. The developed digital models can be used in design. The modeling technique is universal and can be used to calculate the modes of power supply systems of any configuration and traction networks of various designs.